Older adult psychopathology: international comparisons of self-reports, collateral reports, and cross-informant agreement - Leslie A, Rescola; Portillo Reyes, Veronica; Almeida, Vera; Masha, Ivanova; Achenbach, Thomas; Anafarta-Sendag, Meltem; Bite, Leva; Caldas, Carlos; Capps, John; Chen, Yi-Chuen; Colombo, Paola; da Silva Oliveira, Margareth; et al. (2020)
Objectives: To conduct international comparisons of self-reports, collateral reports, and cross-informant agreement regarding older adult psychopathology. Participants: We compared self-ratings of problems (e.g. I cry a lot) and personal strengths (e.g. I like to help others) for 10,686 adults aged 60–102 years from 19 societies and collateral ratings for 7,065 of these adults from 12 societies. Measurements: Data were obtained via the Older Adult Self-Report (OASR) and the Older Adult Behavior Checklist (OABCL; Achenbach et al., 2004) Results: Cronbach’s alphas were .76 (OASR) and .80 (OABCL) averaged across societies. Across societies, 27 of the 30 problem items with the highest mean ratings and 28 of the 30 items with the lowest mean ratings were the same on the OASR and the OABCL. Q correlations between the means of the 0–1–2 ratings for the 113 problem items averaged across all pairs of societies yielded means of .77 (OASR) and .78 (OABCL). For the OASR and OABCL, respectively, analyses of variance (ANOVAs) yielded effect sizes (ESs) for society of 15% and 18% for Total Problems and 42% and 31% for Personal Strengths, respectively. For 5,584 cross-informant dyads in 12 societies, cross-informant correlations averaged across societies were .68 for Total Problems and .58 for Personal Strengths. Mixed-model ANOVAs yielded large effects for society on both Total Problems (ES = 17%) and Personal Strengths (ES = 36%). Conclusions: The OASR and OABCL are efficient, low-cost, easily administered mental health assessments that can be used internationally to screen for many problems and strengths